Analysis of the velocity field behind the measurement orifice using the PIV method - Tomaszewska-Wach, Barbara (Instal, 2025)
was carried out using the PIV method, which involves tracking the movement of tracer particles introduced into the fluid. The use of particle image velocimetry makes it possible to visualize and analyze the velocity field over the entire flow area. Orifice flowmeters, due to their simple design and uncomplicated measurement, are often used in many industries. Two orifices, a standard orifice and a slotted orifice, which were characterized by an equal constriction of 0.5, were tested. The purpose of the experimental study was to see how the shape of the flow holes in the orifice affects the distribution of fluid velocity behind it. The results showed that the shape of the orifice holes has a significant effect on the velocity distribution. In the case of a standard orifice, a clear increase in velocity was observed in the center of the pipe, while a slotted orifice provided a more uniform velocity distribution across the cross-section of the pipeline. This effect is due to the presence of slots over the entire surface of the orifice allowing smooth passage of the flow and reducing turbulence. The article emphasizes the importance of research into innovative solutions in the field of flowmeters, as well as the use of modern measurement techniques such as particle image velocimetry.
Keywords: PIV; slotted orifice; standard orifice; venturi flowmeter